Evaluating Sleep Disorders in Pregnancy and Their Association with Gestational Hypertension - Nadeem, Habibah; Naqvi, Rahat Fatima; Amjad, Maryam; Ali, Muhammad Mussadiq; Kousar, Shermeen; Saad, Abdullah (Indus Journal of Bioscience Research, 2025)
This research investigates the prevalence and severity of sleep disorders encountered during pregnancy and their relation to gestational hypertension, specifically physiological mechanisms responsible for increased blood pressure in pregnant women. Carried out with 159 pregnant women in Punjab, Pakistan, the study used a quantitative, cross-sectional approach with structured questionnaires to evaluate sleep habits, insomnia symptoms, restless legs syndrome (RLS), daytime sleepiness, and obstructive sleep apnea (OSA), and blood pressure measurements to detect cases of gestational hypertension. The findings were that 47.2% of patients reported insomnia, 31.4% reported RLS, 18.9% reported excessive daytime sleepiness, and 9.4% reported OSA, with a high percentage of these patients also diagnosed as having gestational hypertension—especially 60% of OSA and 40% of insomnia patients. The physiological mechanisms connecting poor sleep with hypertension were established as heightened sympathetic nervous system activity, oxidative stress, endothelial dysfunction, and increased levels of pro-inflammatory cytokines, all of which contribute to fluid retention and vascular resistance and hence increased blood pressure during pregnancy. These results underscore the need for early sleep disorder screening and treatment as a routine part of prenatal care to mitigate risks related to pregnancy-associated hypertensive complications. The research underlines the need to incorporate sleep health into maternal healthcare policy and recommends more investigation into specific interventions that might enhance both sleep quality and pregnancy outcomes.